Chinese character metadata: the key to ensure consistency for cataloguing and discoverability of Chinese–language materials. (10th April 2015) - Li, Yu Lilly; Cho, Allan
Using Romanisation system to create metadata for Chinese–language materials causes inconsistency of metadata owing to lack of a unified Romanisation system. Unlike English, Chinese language has a strong distinction between Chinese written language and spoken language. The many different Chinese spoken languages make it hard to standardise the Chinese Romanisation system. While Chinese written language, a.k.a., Chinese characters, offers a hopeful solution to ensure the consistency of metadata, because it has been standardised since Qin Dynasty (221–206 BC) and it has linked people who have locally different spoken languages for about 2, 000 years. In this paper, we will discuss the importance of Chinese character metadata; analyse the challenges and opportunities of creating Chinese character metadata and present University of British Columbia's efforts in creating English and Chinese bilingual metadata to ensure consistency for cataloguing and discoverability of Chinese–language materials.